Khaá¹£Äiá¹£ al-AmthÄl fÄ« al-QurÄn wa AghrÄá¸uhÄ wa al-Mauá¸Å«Ät allatÄ« âÄlajathÄ - Chirzin, Muhammad (Al-Jamiah: Journal of Islamic Studies, 2004)
Â The Quran, as a guidance for human being, consists of some metaphors (amthal) which can be used by those who would think of it. Metaphor is a means of the Quran to convey its ideas related to any things which lead human being to a better life. Metaphor is able to describe Islamic values better and, even, as it is happened to humans daily life. Therefore, a number of Islamic scholars have studied metaphors in the Quran deeply and seriously as carried out by al-HakÄ«m al-TarmizÄ«, al-MawardÄ«, ibn Qayyim al-Jawziyya, Az ZarkaszÄ«, as-SuyÅ«tÄ« and others. Knowledge about metaphor in the QurÄn is very significant. Therefore, it is not an exaggeration when ash-ShÄfiâÄ« states that a mujtahid should know about metaphor of the QurÄn. This article tries to explore some opinions of Muslim scholars about metaphor in the QurâÄn with abroad view of its meaning, purposes and characteristics. Â